Characterization of holins, the membrane proteins of coliphage ASEC2201: a genomewide in silico approach - Saeed, Humaira; Padmesh, Sudhaker; Singh, Aditi; Singh, Sujeet Pratap; Siddiqui, Mohammed Haris; Sen, Manodeep; Hussain, Imran; Beg, Mirza Masroor Ali (Frontiers in Microbiology, 2025)
Drug-resistant Escherichia coli poses a significant healthcare burden, driving the search for novel antimicrobials. We have previously done the isolation and whole-genome sequencing of ASEC2201, a novel coliphage derived from multidrug-resistant clinical E. coli strains. Here, we report the identification and characterization of phage enzyme, holin by in silico approaches. Genome annotation using Prokka identified three putative holin genes (PROKKA_03659, PROKKA_04292, and PROKKA_04422) belonging to the Phage_holin_2_1 superfamily. Upstream promoter prediction revealed active regulatory elements at positions 112, 177, and 186 for these genes, indicating robust transcriptional activity. Transmembrane topology analysis using DeepTMHMM confirmed the presence of two to three α-helical membrane-spanning domains in each holin, essential for pore formation. Homology modeling with SWISS-MODEL yielded high-confidence three-dimensional structures characterized by conserved membrane-anchoring motifs, as supported by QMEAN and GMQE quality scores. In silico identification of cell-penetrating peptide motifs within the holin sequences suggests potential for enhanced intracellular delivery in CPP-fusion therapeutic constructs. Overall, our in-depth analysis elucidates the structural and functional properties of ASEC2201 holins, underscoring their biotechnological significance as scaffolds for developing novel antimicrobial strategies against MDR E. coli. It gives us an understanding on how the holins, with their inherent membrane-disrupting functions, can be explored in detail for future use as lysis modules in programmable bacterial systems, while their identified CPP motifs offer additional potential for engineering targeted therapeutic delivery vehicles. This study also demonstrates the potential of integrative in silico approaches in developing a comprehensive foundation for future experimental validation for proteins with no prior functional annotation.